Propriedades dielétricas intrínsecas de perovskitas duplas RE2CoMnO6 (RE = íon terra-rara) - Barbosa, Rafael de Lima (2017)
Dielectric ceramics with ordered double perovskite structure and RE2CoMnO6 stoichiometry, in which RE is a rare-earth ion, are usually multiferroic with critical magnetic and electrical transition temperatures depending on the RE ion. This family of materials crystallizes in the P21/n symmetry when there is ordering of the Mn and Co ions. This monoclinic structure has a distortion directly dependent on the RE ionic size, influencing directly the properties of these materials. In this work, we investigate the intrinsic dielectric properties of these samples for RE = Tb, Dy, Ho, Yb and Tm. These properties were investigated by infrared reflection spectroscopy, allowing to estimate both the intrinsic static dielectric constant and the dielectric losses due to the polar phonons, which allows estimating the maximum microwave quality factor obtained when a resonator is formed with the respective materials. Our results show that, as obtained for La2CoMnO6 (LaCMO), the main compound of this family, the intrinsic static dielectric constant is reduced. In the case of LaCMO, dielectric measurements performed by other authors showed a colossal effect, whose origin was extrinsic effects. Therefore, our result allows to predict that any effect that leads to very high dielectric constants is extrinsic in this family of materials. In addition, the analysis of the quality factor showed that such ceramics have a quality factor compatible with those employed in microwave dielectric resonators since the low dielectric constant is not a problem.